1996
DOI: 10.1172/jci118928
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional evidence for in vitro cytokine enhancement of human and murine target cell sensitivity to glucocorticoids. TNF-alpha priming increases glucocorticoid inhibition of TNF-alpha-induced cytotoxicity/apoptosis.

Abstract: Cytokine-induced glucocorticoid secretion and glucocorticoid inhibition of cytokine synthesis and pleiotropic actions act as important safeguards in preventing cytokine overreaction. We found that TNF-␣ increased glucocorticoid-induced transcriptional activity of the glucocorticoid receptor (GR) via the glucocorticoid response elements (GRE) in L-929 mouse fibroblasts transfected with a glucocorticoid-inducible reporter plasmid. In addition, TNF-␣ also enhanced GR number. The TNF-␣ effect on transcriptional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
15

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 54 publications
3
58
0
15
Order By: Relevance
“…54 In agreement with these data, it has been reported that treatment of A549 cells with TNF-␣ targeted GR, possibly by phosphorylation, to remain in cytoplasm. 55 However, TNF-␣ increased the GR number and glucocorticoidinduced transcriptional activity of the GR in L-929 mouse fibroblast, 56 which is in contradiction with the above data. These divergences can reflect different genetic cell programs, because TNF-␣ is toxic in L-929 cells.…”
Section: Discussionmentioning
confidence: 66%
“…54 In agreement with these data, it has been reported that treatment of A549 cells with TNF-␣ targeted GR, possibly by phosphorylation, to remain in cytoplasm. 55 However, TNF-␣ increased the GR number and glucocorticoidinduced transcriptional activity of the GR in L-929 mouse fibroblast, 56 which is in contradiction with the above data. These divergences can reflect different genetic cell programs, because TNF-␣ is toxic in L-929 cells.…”
Section: Discussionmentioning
confidence: 66%
“…TNF-a was initially identified as a protein capable of inducing necrosis in mouse solid tumors (Larrick and Wright, 1990) and apoptosis in several different cell lines (Beg and Baltimore, 1996;Costas et al, 1996Costas et al, , 2000Liu et al, 1996;Wang et al, 1998;Franco et al, 2002). Herein, we demonstrated that this inflammatory cytokine does not induce breast ductal tumor cell apoptosis, even in the presence of the NF-kB inhibitor SZ, in a dose that significantly inhibits this transcription factor binding to its specific DNA sequence.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, it has been demonstrated that several cell lines are not sensitive to the proapoptotic signal unless the novo synthesis of antiapoptotic NF-kB target genes is blocked (Beg and Baltimore, 1996;Costas et al, 1996Costas et al, , 2000Liu et al, 1996;Wang et al, 1998;Franco et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is supported by findings of a direct correlation between the concentration of GR in a target cell and the sensitivity of this cell to glucocorticoids (10). In addition, the cell concentration of GR has been already shown to be modulated by a number of mediators including glucocorticoids, cAMP-inducing agonists, and cytokines such as TNF-␣ and interleukin-2, -4, and -13 (11)(12)(13)(14)(15). We found that somatostatin increases glucocorticoid binding and signaling in RAW 264.7 macrophages.…”
mentioning
confidence: 83%